2018
DOI: 10.3390/healthcare6030074
|View full text |Cite
|
Sign up to set email alerts
|

Functionality in Middle-Aged and Older Overweight and Obese Individuals with Knee Osteoarthritis

Abstract: Patients with knee osteoarthritis (OA) suffer from immobility and pain. The objective of this cross-sectional study was to investigate the relationship between pain and functionality in middle-aged and older overweight and obese individuals with mild-to-moderate knee OA. Overall pattern, physical activity, and total energy expenditure (TEE) were assessed in 83 participants. The Western Ontario McMaster Universities Arthritis Index (WOMAC) was used to assess lower extremity pain and function. The six-minute wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…In the study by Cetin et al (2009), womenʼs total LI scores were significantly elevated. Using the Western Ontario and McMaster Universities (WOMAC) scale, which is similar to the LI scale, Akhavan et al (2018) found higher scores in women for physical functionality and performance of daily activities. In our study, FES scores associated with falling and fear of falling were lower in women, and there was a negative correlation between LI and FES scores (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Cetin et al (2009), womenʼs total LI scores were significantly elevated. Using the Western Ontario and McMaster Universities (WOMAC) scale, which is similar to the LI scale, Akhavan et al (2018) found higher scores in women for physical functionality and performance of daily activities. In our study, FES scores associated with falling and fear of falling were lower in women, and there was a negative correlation between LI and FES scores (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…play an important role while the patients are answering questions which may explain the subjectivity of answers to the questions asked . [10] Thus to avoid this factor 6MWT and 6PBRT were assessed to evaluate energy expenditure and exercise capacity of patients with osteoarthritis of knee. Factors such as weight bearing pain, joint instability sometimes mask patient's functional capacity since 6MWT incorporates weight bearing activity and increased weight bearing in turn increases pain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies 21,22 have investigated the individual relationship between these abilities and perceived HRQOL, the authors are not aware of any studies on the main databases that concomitantly assessed the main daily transfer activities performed by this population, understood as global physical capacity. We found the ability to walk long distances adjusted for BMI explained 22.3% of HRQOL in the pain domain of the older adults with symptomatic KOA.…”
Section: Discussionmentioning
confidence: 99%